Comprehensive Utilization and Optimal Allocation of Environmental Protection Building Materials in the Construction of Civil Engineering - Li Ren; Huasha Ru; Ruiya Xiao; Yao Ju (Journal of Applied Science and Engineering, 2026)
With the increasing global awareness of environmental protection and the deepening of sustainable development, the construction industry faces new challenges and opportunities. Applying environmentally friendly building materials in civil engineering construction is not only a response to the requirements of global green development but also a meaningful way to improve construction quality and reduce project costs. The research methodology includes a multi-criteria decision-making approach, integrating material selection criteria such as mechanical properties, sustainability, cost, and environmental impact. An optimization model, using genetic algorithms and life cycle assessment, was employed to achieve the best material distribution for specific project needs. The model was calibrated and validated with data from several case studies to ensure practical applicability. The research results show that through scientific and reasonable material optimization allocation, the utilization rate of materials can be further improved, the construction efficiency can be improved, the overall construction cost can be reduced, and the carbon emission can be reduced by more than 20%, which provides an essential reference for the sustainable development of civil engineering construction.